Effects of growth regulators on the fruiting of strawberry cultivar "Monte alegre" - Castro, Paulo R. C.; MinamiI, Keigo; Vello, Natal A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
The effects of growth regulators on strawberry cultivar "Monte Alegre" were studied in Piracicaba, State of Sao Paulo. Succinic acid -2,2 - dimethylhydrazide (SADH) 5000 ppm, (2- chloroethyl) trimethylammonium chloride (CCC) 2000 ppm, and gibberellic acid (GA) 550 ppm were sprayed, and also three applications of indoleacetic acid (IAA) 10 ppm or GA 10 ppm were made. It was verified that although GA 550 ppm, SADH and CCC decreased yield, three applications of IAA 10 ppm or GA 10 ppm have promoted a tendency to increase strawberry yield. It was noted that growth regulators do not alter number of fruit, and GA 550 ppm promotes reduction in fruit mean weight. GA ppm increased number of fruit on 3rd and 4th weeks of harvesting, decreasing progressively in subsequent weeks. It was observed that GA 10 ppm or IAA 10 ppm promotes an increase in peduncle length, casing harvesting.